MEK-inhibitor treatment reduces the induction of regulatory T cells in mice after influenza A virus infection - Koch-Heier, Julia; Vogel, Annette B.; Füll, Yvonne; Ebensperger, Marina; Schönsiegel, Annika; Zinser, Raphael S.; Planz, Oliver (Frontiers in Immunology, 2024)
Regulatory T cells (Tregs) play a crucial and complex role in balancing the immune response to viral infection. Primarily, they serve to regulate the immune response by limiting the expression of proinflammatory cytokines, reducing inflammation in infected tissue, and limiting virus-specific T cell responses. But excessive activity of Tregs can also be detrimental and hinder the ability to effectively clear viral infection, leading to prolonged disease and potential worsening of disease severity. Not much is known about the impact of Tregs during severe influenza. In the present study, we show that CD4+/CD25+FoxP3+ Tregs are strongly involved in disease progression during influenza A virus (IAV) infection in mice. By comparing sublethal with lethal dose infection in vivo, we found that not the viral load but an increased number of CD4+/CD25+FoxP3+ Tregs may impair the immune response by suppressing virus specific CD8+ T cells and favors disease progression. Moreover, the transfer of induced Tregs into mice with mild disease symptoms had a negative and prolonged effect on disease outcome, emphasizing their importance for pathogenesis. Furthermore, treatment with MEK-inhibitors resulted in a significant reduction of induced Tregs in vitro and in vivo and positively influenced the progression of the disease. Our results demonstrate that CD4+/CD25+FoxP3+ Tregs are involved in the pathogenesis of severe influenza and indicate the potential of the MEK-inhibitor zapnometinib to modulate CD4+/CD25+FoxP3+ Tregs. Thus, making MEK-inhibitors even more promising for the treatment of severe influenza virus infections.